1988
DOI: 10.1001/archderm.1988.01670120011002
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocyte Subsets in the Lesional Skin of Allogeneic and Autologous Bone Marrow Transplant Patients

Abstract: Cutaneous biopsy specimens obtained from bone marrow transplant (BMT) patients, most with graft-vs-host disease (GVHD), were analyzed for infiltration by helper, cytotoxic, and suppressor T lymphocytes and natural killer cells. Lesional skin from patients with early mild GVHD and drug reactions showed a CD4/CD8 ratio of 5.0 or more, but later biopsy specimens from patients with acute GVHD and the majority of sections from those with chronic GVHD showed a CD4/CD8 ratio of 0.8 to 3.0 due to increased numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Immunohistochemistry Lymphocyte subsets, natural killer cells, and mIL-12 were detected in frozen tumor tissue sections using immunohistochemical staining as previously described (Paller et al, 1988), using rat monoclonal anti-CD8 or anti-CD4, mouse monoclonal anti-natural killer cell, or rabbit polyclonal anti-mIL-12 antibodies (Pharmigen, Piscataway, NJ), and detected by 3Ј,3Ј-diaminobenzidine-H 2 O 2 staining. Mouse spleen was used as positive control tissue.…”
Section: Murine Tumor Modelmentioning
confidence: 99%
“…Immunohistochemistry Lymphocyte subsets, natural killer cells, and mIL-12 were detected in frozen tumor tissue sections using immunohistochemical staining as previously described (Paller et al, 1988), using rat monoclonal anti-CD8 or anti-CD4, mouse monoclonal anti-natural killer cell, or rabbit polyclonal anti-mIL-12 antibodies (Pharmigen, Piscataway, NJ), and detected by 3Ј,3Ј-diaminobenzidine-H 2 O 2 staining. Mouse spleen was used as positive control tissue.…”
Section: Murine Tumor Modelmentioning
confidence: 99%
“…Kaye et al (13) reponed that the CD4/CD8 ratio varies in different patients; only one of three patients with chronic GVHD they studied showed a CD4/CD8 ratio larger than unity. Paller et al (14) also reponed that the CD4/CD8 ratio was from 2.3 to 6.6 in chronic GVHD but tended to be lower in the acute form. It is suggested that the helper T cells may produce local factors that stimulate the differentiation of precursor cells to cytotoxic T cells into the lesion.…”
Section: Gvhd Is a Life-threatening Complication Of Heterologous Bonementioning
confidence: 99%
“…While many studies have been conducted to determine the nature of the lymphocyte subpopulations found in the skin of patients with acute GVHD, unfortunately, the results are inconclusive at best (72–84). The infiltrate is composed of T cells, but both CD4+ and CD8+ subsets have shown to predominate (72–84).…”
Section: Acute Gvhdmentioning
confidence: 99%
“…While many studies have been conducted to determine the nature of the lymphocyte subpopulations found in the skin of patients with acute GVHD, unfortunately, the results are inconclusive at best (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). The infiltrate is composed of T cells, but both CD4+ and CD8+ subsets have shown to predominate (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). In recent years, plasma and urine proteomics have shown promise in enabling early diagnosis of acute GVHD (85)(86)(87)(88).…”
Section: Diagnosismentioning
confidence: 99%